Development and validation of MonteRay, a fast Monte Carlo dose engine for carbon ion beam radiotherapy - Lysakovski, Peter; Kopp, Benedikt; Tessonnier, Thomas; Mein, Stewart; Ferrari, Alfredo; Haberer, Thomas; Debus, Jürgen; Mairani, Andrea (Medical physics, 2023)
Background Monte Carlo (MC) simulations are considered the gold-standard for accuracy in radiotherapy dose calculation; so far however, no commercial treatment planning system (TPS) provides a fast MC for supporting clinical practice in carbon ion therapy. Purpose To extend and validate the in-house developed fast MC dose engine MonteRay for carbon ion therapy, including physical and biological dose calculation. Methods MonteRay is a CPU MC dose calculation engine written in C that is capable of simulating therapeutic proton, helium and carbon ion beams. In this work, development steps taken to include carbon ions in MonteRay are presented. Dose distributions computed with MonteRay are evaluated using a comprehensive validation dataset, including various measurements (pristine Bragg peaks, spread out Bragg peaks in water and behind an anthropomorphic phantom) and simulations of a patient plan. The latter includes both physical and biological dose comparisons. Runtimes of MonteRay were evaluated against those of FLUKA MC on a standard benchmark problem. Results Dosimetric comparisons between MonteRay and measurements demonstrated good agreement. In terms of pristine Bragg peaks, mean errors between simulated and measured integral depth dose distributions were between −2.3% and +2.7%. Comparing SOBPs at 5, 12.5 and 20 cm depth, mean absolute relative dose differences were 0.9%, 0.7% and 1.6% respectively. Comparison against measurements behind an anthropomorphic head phantom revealed mean absolute dose differences of 1.2%±1.1%\1.2% ± 1.1\;% \;\with global 3%/3 mm 3D-γ passing rates of 99.3%, comparable to those previously reached with FLUKA (98.9%). Comparisons against dose predictions computed with the clinical treatment planning tool RayStation 11B for a meningioma patient plan revealed excellent local 1%/1 mm 3D-γ passing rates of 98% for physical and 94% for biological dose. In terms of runtime, MonteRay achieved speedups against reference FLUKA simulations ranging from 14× to 72×, depending on the beam's energy and the step size chosen. Conclusions Validations against clinical dosimetric measurements in homogeneous and heterogeneous scenarios and clinical TPS calculations have proven the validity of the physical models implemented in MonteRay. To conclude, MonteRay is viable as a fast secondary MC engine for supporting clinical practice in proton, helium and carbon ion radiotherapy.
Gesehen am 14.11.2023